Low-dose digoxin enhances the anticonvulsive potential of carbamazepine and lamotrigine in chemo-induced seizures with different neurochemical mechanisms - Tsyvunin, Vadim; Shtrygol’, Sergiy; Havrylov, Ihnat; Shtrygol’, Diana (ScienceRise: Pharmaceutical Science, 2021)
"Non-antiepileptic" drugs have a strong potential as adjuvants in multidrug-resistant epilepsy treatment. In previous study the influence of low doses of digoxin, which do not affect the myocardium, on the anticonvulsant potential of classical commonly used anti-epileptic drugs under conditions of seizures, induced by pentylenetetrazole and maximal electroshock, has been investigated. The aim of the study was to investigate the influence of digoxin at a sub-cardiotonic dose on the anticonvulsant potential of carbamazepine and lamotrigine in experimental seizures with different neurochemical mechanisms. Material and methods: A total of 192 random-bred male albino mice weighting 22–25 g were used. Carbamazepine and lamotrigine were administered intragastrically in conditionally effective (ED50) and sub-effective (½ ED50) doses: carbamazepine at doses of 100 and 50 mg/kg; lamotrigine at doses of 25 and 12.5 mg/kg. Digoxin was administered subcutaneously at a sub-cardiotonic dose of 0.8 mg/kg as an adjuvant to carbamazepine and lamotrigine in ½ ED50. Picrotoxin (2.5 mg/kg subcutaneously); thiosemicarbazide (25 mg/kg intraperitoneally); strychnine (1.2 mg/kg subcutaneously); camphor (1000 mg/kg intraperitoneally) were used as convulsant agents. Results: It was found that digoxin not only has its own permanent anticonvulsant effect on different models of paroxysms with different neurochemical mechanisms of development, but also significantly enhances the anticonvulsant potential of carbamazepine (to a lesser extent – lamotrigine) regardless of the pathogenesis of experimental paroxysms. Conclusion: Based on the results, it can be concluded that digoxin has a high potential as an adjuvant medicine in complex epilepsy treatment because it enhances the efficiency of low-dose traditional anticonvulsants carbamazepine and lamotrigine